Proton conductive cell structure, proton conductor, electrochemical device, and method for producing proton conductor
The proton conductive cell structure with a graded Sr/Ba ratio in the solid electrolyte layer addresses the high resistance and low ion transfer issues of existing proton-conducting metal oxides, improving the efficiency of fuel cells and steam electrolysis cells.
Patent Information
- Application Number
- JP2022532457
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-18
- Filing Date
- 2021-05-28
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-05-28
AI Technical Summary
Existing proton-conducting metal oxides like BZY and SZY face issues with high resistance and low ion transfer number, which affect the efficiency of fuel cells and steam electrolysis cells.
A proton conductive cell structure with a solid electrolyte layer composed of Ba_x1Sr_x2A_1-yMyO_3-δ, where A is Zr or Hf, M is Y or other rare earth elements, and oxygen vacancies satisfy 0.95≦x1+x2≦1.10, 0
The structure achieves a high ion transfer number and low resistance, enhancing the performance of fuel cells and steam electrolysis cells by maintaining low resistance while increasing ion conductivity.
Smart Images

Figure 0007609164000008 
Figure 0007609164000009 
Figure 0007609164000010
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a proton conducting cell structure, a proton conductor, an electrochemical device, and a method for producing a proton conductor. This application claims priority to Japanese Application No. 2020-104994, filed on June 18, 2020, and incorporates by reference all of the contents of said Japanese application. [Background technology]
[0002] As a solid electrolyte applicable to PCFCs (Protonic Ceramic Fuel Cells, proton conductive oxide fuel cells) that use hydrogen ions (protons) as charge carriers, proton conductive metal oxides having a perovskite structure are known (for example, Patent Documents 1 to 4). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2001-307546 A [Patent Document 2] JP 2007-197315 A [Patent Document 3] JP 2016-103409 A [Patent Document 4] JP 2016-160111 A Summary of the Invention
[0004] The proton conductive cell structure of the present disclosure is a cell structure including an air electrode, a hydrogen electrode, and a solid electrolyte layer interposed between the air electrode and the hydrogen electrode, the solid electrolyte layer includes at least a first solid electrolyte layer made of a dense material, The first solid electrolyte layer is It has a perovskite structure and the following formula (1): Ba x1 Sr x2 A 1-y M y O 3-δ (1) (wherein element A is at least one selected from the group consisting of Zr, Ce, and Hf, element M is at least one selected from the group consisting of Y, Yb, Er, Ho, Tm, Gd, In, and Sc, δ is the amount of oxygen deficiency, satisfying 0.95 ≦ x1 + x2 ≦ 1.10 and 0 < y ≦ 0.5) and contains a metal oxide represented by the ratio of Sr to the total amount of Ba and Sr (Sr / [Ba + Sr]: atomic number basis) in the vicinity of the surface on the air electrode side of the first solid electrolyte layer is 0.4 or more, and the ratio of Sr to the total amount of Ba and Sr (Sr / [Ba + Sr]) in the vicinity of the surface on the hydrogen electrode side of the first solid electrolyte layer is 0.003 or more and 0.3 or less.
[0005] The proton conductor of the present disclosure is a proton conductor used as the first solid electrolyte layer in the proton conduction type cell structure of the present disclosure, which is a layer-like substance composed of a dense material, has a perovskite structure, and has the following formula (1): Ba x1 Sr x2 A 1-y M y O 3-δ (1) (wherein element A is at least one selected from the group consisting of Zr, Ce, and Hf, element M is at least one selected from the group consisting of Y, Yb, Er, Ho, Tm, Gd, In, and Sc, δ is the amount of oxygen deficiency, satisfying 0.95 ≦ x1 + x2 ≦ 1.10 and 0 < y ≦ 0.5) and contains a metal oxide represented by the ratio of Sr to the total amount of Ba and Sr (Sr / [Ba + Sr]: atomic number basis) in the vicinity of the first main surface is 0.4 or more, and In the vicinity of the second main surface, the ratio of Sr to the total amount of Ba and Sr (Sr / [Ba + Sr]) is 0.003 or more and 0.3 or less.
[0006] The electrochemical device of the present disclosure includes the proton-conducting cell structure of the present disclosure.
[0007] One of the methods for manufacturing the proton conductor of the present disclosure is a method for manufacturing a proton conductor used as the first solid electrolyte layer of the proton-conducting cell structure of the present disclosure, having a perovskite structure and represented by the following formula (2): Ba x1 A 1-y M y O 3-δ (2) (In the formula, element A is at least one selected from the group consisting of Zr, Ce, and Hf, element M is at least one selected from the group consisting of Y, Yb, Er, Ho, Tm, Gd, In, and Sc, δ is the amount of oxygen deficiency, satisfying 0.95 ≦ x1 ≦ 1.10, 0 < y ≦ 0.5) onto the surface on the air electrode side of the first solid electrolyte precursor layer containing a metal oxide represented by having a perovskite structure and represented by the following formula (3): Sr x2 A 1-y M y O 3-δ (3) (In the formula, element A is at least one selected from the group consisting of Zr, Ce, and Hf, element M is at least one selected from the group consisting of Y, Yb, Er, Ho, Tm, Gd, In, and Sc, δ is the amount of oxygen deficiency, satisfying 0.95 ≦ x2 ≦ 1.10, 0 < y ≦ 0.5) contacting a mixture of a powder of a metal oxide represented by and a powder of a strontium compound, and heat-treating the mixture at 1200 to 1400 °C in that state, including the step.
[0008] Another method for manufacturing the proton conductor of the present disclosure is a method for manufacturing a proton conductor used as the solid electrolyte layer of the proton conduction type cell structure of the present disclosure, having a perovskite structure and represented by the following formula (2): Ba x1 A 1-y M y O 3-δ (2) (In the formula, element A is at least one selected from the group consisting of Zr, Ce, and Hf, element M is at least one selected from the group consisting of Y, Yb, Er, Ho, Tm, Gd, In, and Sc, δ is the amount of oxygen deficiency, satisfying 0.95 ≦ x1 ≦ 1.10 and 0 < y ≦ 0.5) onto the surface on the air electrode side of the first solid electrolyte precursor layer containing a metal oxide represented by having a perovskite structure and represented by the following formula (3): Sr x2 A 1-y M y O 3-δ (3) (In the formula, element A is at least one selected from the group consisting of Zr, Ce, and Hf, element M is at least one selected from the group consisting of Y, Yb, Er, Ho, Tm, Gd, In, and Sc, δ is the amount of oxygen deficiency, satisfying 0.95 ≦ x2 ≦ 1.10 and 0 < y ≦ 0.5) a paste containing a powder of a metal oxide represented by, a powder of a strontium compound, and a binder is applied, and heat treatment is performed at 1200 to 1400 °C in that state, including the step.
Brief Description of the Drawings
[0009] [Figure 1] FIG. 1 is a diagram schematically showing an example of a proton conduction type cell structure according to the present disclosure. [Diagram 2] FIG. 2 is a diagram schematically showing another example of a proton conduction type cell structure according to the present disclosure. [Figure 3A] FIG. 3A is a diagram showing the element ratio of Ba to Sr in the solid electrolyte layer formed in Example 1. [Figure 3B] FIG. 3B is a partially enlarged view of FIG. 3A. [Figure 4A] FIG. 4A is a diagram showing the element ratio of Ba to Sr in the solid electrolyte layer formed in Example 2. [Figure 4B] FIG. 4B is a partially enlarged view of FIG. 4A. [Diagram 5] FIG. 5 is a diagram showing the element ratio of Ba to Sr in the solid electrolyte layer formed in Example 3. As shown in FIG. [Figure 6] FIG. 6 is a diagram showing the element ratio of Ba to Sr in the solid electrolyte layer formed in Example 4. As shown in FIG. [Figure 7] FIG. 7 is a diagram showing the element ratio of Ba to Sr in the solid electrolyte layer formed in Comparative Example 3. As shown in FIG. [Figure 8] FIG. 8 is a diagram showing the element ratio of Ba to Sr in the solid electrolyte layer formed in Comparative Example 4. As shown in FIG. [Figure 9] FIG. 9 is a diagram showing an equivalent circuit of a proton conductive cell structure assuming hole conduction. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] [Problem that this disclosure aims to solve] Barium zirconate doped with yttrium (BZY) is one of the proton-conducting metal oxides, and because it exhibits good proton conductivity even at temperatures below 700°C, it is expected to be used as a solid electrolyte for intermediate-temperature fuel cells and steam electrolysis cells. However, hole conduction occurs in BZY in an oxygen atmosphere, which can reduce the electromotive force due to leakage current and the current efficiency during steam electrolysis. Strontium zirconate doped with yttrium (SZY) is also a proton-conducting metal oxide. Although SZY exhibits a higher ion transport number than BZY, it also has an extremely high resistance, which makes it unsuitable for use in fuel cells.
[0011] An object of the present disclosure is to provide a proton conductor capable of achieving both a high ion transport rate and a low resistance value. [Effects of the Present Disclosure]
[0012] According to the present disclosure, it is possible to provide a proton conductor capable of achieving both a high ion transport rate and a low resistance value, and a method for manufacturing the same. Further, according to the present disclosure, it is possible to provide a proton-conducting cell structure using the above proton conductor, and an electrochemical device including the above proton-conducting cell structure.
[0013] [Description of Embodiments] First, the content of the present disclosure will be listed and described. (1) The proton-conducting cell structure according to the present disclosure is a cell structure including an air electrode, a hydrogen electrode, and a solid electrolyte layer interposed between the air electrode and the hydrogen electrode, wherein the solid electrolyte layer includes at least a first solid electrolyte layer made of a dense material, the first solid electrolyte layer, has a perovskite structure and the following formula (1): Ba x1 Sr x2 A 1-y M y O 3-δ (1) (In the formula, the element A is at least one selected from the group consisting of Zr, Ce, and Hf, the element M is at least one selected from the group consisting of Y, Yb, Er, Ho, Tm, Gd, In, and Sc, δ is the amount of oxygen deficiency, satisfying 0.95 ≦ x1 + x2 ≦ 1.10 and 0 < y ≦ 0.5) and includes a metal oxide represented by the ratio of Sr to the total amount of Ba and Sr (Sr / [Ba + Sr]: atomic number basis) in the vicinity of the surface on the air electrode side of the first solid electrolyte layer is 0.4 or more, and The ratio of Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]) in the vicinity of the surface on the hydrogen electrode side of the first solid electrolyte layer is 0.003 or more and 0.3 or less.
[0014] The proton conducting cell structure described above in (1) includes a solid electrolyte layer that contains the metal oxide represented by the above formula (1) and has a Ba to Sr content gradient such that Ba increases and Sr decreases from the surface on the air electrode side toward the inside of the solid electrolyte layer. This makes it possible to increase the ion transport number while maintaining a low resistance, as compared with a proton conducting cell structure having a solid electrolyte layer made of BZY. Therefore, the proton conductive cell structure is suitable for providing a fuel cell or the like which achieves both a high ion transport number and high output.
[0015] (2) In the proton conductive cell structure of (1) above, it is preferable that the ratio of Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]) at the center in the thickness direction of the first solid electrolyte layer is 0.005 or more and 0.3 or less. In this case, it is more suitable for increasing the ion transport number while maintaining a low resistance.
[0016] (3) In the proton conductive cell structure of (1) or (2) above, the first solid electrolyte layer preferably has a ratio of Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]) of 0.3 or more in a region of 6% of the total thickness from the surface on the air electrode side toward the hydrogen electrode side in the thickness direction. This case is also suitable for increasing the ion transport number while maintaining a low resistance.
[0017] (4) In any of the proton conductive cell structures (1) to (3) above, in the metal oxide of the formula (1) above, it is preferable that 50 at % (atomic percent) or more of element A is Zr, and element M is Y. By making half or more of element A Zr, chemical stability can be improved. By making element M Y, proton conductivity can be improved.
[0018] (5) In any of the proton-conducting cell structures of (1) to (3) above, the solid electrolyte layer further includes a porous second solid electrolyte layer interposed between the first solid electrolyte layer and the air electrode. The second solid electrolyte layer has a perovskite structure and the following formula (1): Ba x1 Sr x2 A 1-y M y O 3-δ (1) (In the formula, element A is at least one selected from the group consisting of Zr, Ce, and Hf, element M is at least one selected from the group consisting of Y, Yb, Er, Ho, Tm, Gd, In, and Sc, δ is the oxygen deficiency amount, satisfying 0.95 ≦ x1 + x2 ≦ 1.10 and 0 < y ≦ 0.5) and preferably contains a metal oxide represented by In this case, in the solid electrolyte layer constituting the proton-conducting cell structure, the three-phase interface of the air electrode material, air, and electrolyte can be increased, and the electrode activity can be improved. Therefore, the proton-conducting cell structure further has a good ion transport rate.
[0019] (6) In the proton-conducting cell structure of (5) above, in the metal oxide of the formula (1), it is preferable that 50 at% or more of element A is Zr and element M is Y. By making more than half of element A be Zr, the chemical stability can be enhanced. By making element M be Y, the proton conductivity can be increased.
[0020] (7) The proton conductor according to the present disclosure is a proton conductor used as the first solid electrolyte layer in the proton-conducting cell structure of the present disclosure, is a layer-like material made of a dense material, has a perovskite structure and the following formula (1): Ba x1 Sr x2 A 1-y M y O3-δ (1) (In the formula, element A is at least one selected from the group consisting of Zr, Ce, and Hf, element M is at least one selected from the group consisting of Y, Yb, Er, Ho, Tm, Gd, In, and Sc, δ is the amount of oxygen deficiency, satisfying 0.95 ≦ x1 + x2 ≦ 1.10, 0 < y ≦ 0.5) and contains a metal oxide represented by In the vicinity of the first main surface, the ratio of Sr to the total amount of Ba and Sr (Sr / [Ba + Sr]: atomic number basis) is 0.4 or more, and in the vicinity of the second main surface, the ratio of Sr to the total amount of Ba and Sr (Sr / [Ba + Sr]) is 0.003 or more and 0.3 or less. The proton conductor of (7) above has low resistance and a high ion transport rate.
[0021] (8) In the proton conductor of (7) above, it is preferable that the ratio of Sr to the total amount of Ba and Sr (Sr / [Ba + Sr]) in the central part in the thickness direction is 0.005 or more and 0.3 or less. (9) In the proton conductor of (7) or (8) above, in the region of 6% of the total thickness from the first main surface side to the second main surface side in the thickness direction, the ratio of Sr to the total amount of Ba and Sr (Sr / [Ba + Sr]) is preferably 0.3 or more. (10) In any of the proton conductors of (7) to (9) above, in the metal oxide of the above formula (1), it is preferable that 50 at% or more of element A is Zr and element M is Y. By using the proton conductor of (7) to (10) above, a proton conductive cell structure of the present disclosure can be provided.
[0022] (11) The electrochemical device according to the present disclosure includes any of the proton conductive cell structures of (1) to (6) above. The electrochemical device includes a solid electrolyte layer having low resistance and a high ion transport rate. The above-mentioned electrochemical device is, for example, a fuel cell, a steam electrolysis cell, or a gas decomposition device.
[0023] (12) The method for producing a proton conductor according to the present disclosure is a method for producing a proton conductor used as the first solid electrolyte layer of any one of the proton-conducting cell structures of (1) to (4) above, having a perovskite structure and represented by the following formula (2): Ba x1 A 1-y M y O 3-δ (2) (In the formula, element A is at least one selected from the group consisting of Zr, Ce, and Hf, element M is at least one selected from the group consisting of Y, Yb, Er, Ho, Tm, Gd, In, and Sc, δ is the amount of oxygen deficiency, satisfying 0.95 ≦ x1 ≦ 1.10 and 0 < y ≦ 0.5) on the surface of the air electrode side of the first solid electrolyte precursor layer containing a metal oxide represented by having a perovskite structure and represented by the following formula (3): Sr x2 A 1-y M y O 3-δ (3) (In the formula, element A is at least one selected from the group consisting of Zr, Ce, and Hf, element M is at least one selected from the group consisting of Y, Yb, Er, Ho, Tm, Gd, In, and Sc, δ is the amount of oxygen deficiency, satisfying 0.95 ≦ x2 ≦ 1.10 and 0 < y ≦ 0.5) contact a mixture of a powder of a metal oxide represented by and a powder of a strontium compound, and heat-treat the mixture at 1200 to 1400 °C in that state, including the step.
[0024] (13) Another method for producing a proton conductor according to the present disclosure is a method for producing a proton conductor used as the solid electrolyte layer of the proton-conducting cell structure of (5) or (6) above, having a perovskite structure and represented by the following formula (2): Ba x1 A 1-y M y O 3-δ (2) (In the formula, element A is at least one selected from the group consisting of Zr, Ce, and Hf, element M is at least one selected from the group consisting of Y, Yb, Er, Ho, Tm, Gd, In, and Sc, δ is the amount of oxygen deficiency, satisfying 0.95 ≦ x1 ≦ 1.10 and 0 < y ≦ 0.5) on the surface of the air electrode side of the first solid electrolyte precursor layer containing a metal oxide represented by having a perovskite structure and represented by the following formula (3): Sr x2 A 1-y M y O 3-δ (3) (In the formula, element A is at least one selected from the group consisting of Zr, Ce, and Hf, element M is at least one selected from the group consisting of Y, Yb, Er, Ho, Tm, Gd, In, and Sc, δ is the amount of oxygen deficiency, satisfying 0.95 ≦ x2 ≦ 1.10 and 0 < y ≦ 0.5) a paste containing a powder of a metal oxide represented by, a powder of a strontium compound, and a binder is applied, and heat treatment is performed at 1200 to 1400 °C in that state. According to the method for producing a proton conductor of (12) and (13) above, a proton conductor according to the present disclosure can be produced.
[0025] [Details of Embodiments] Specific examples of the embodiments in the present disclosure will be described below with appropriate reference to the drawings. Note that the embodiments of the present invention are not limited to these examples. The scope of the present invention is indicated by the claims, and it is intended that all modifications within the meaning and scope equivalent to the claims are included.
[0026] (First Embodiment) [Proton-conducting cell structure] FIG. 1 is a diagram illustrating a schematic diagram of an example of a proton conductive cell structure according to the present disclosure. The proton conducting cell structure 10 according to this embodiment includes an air electrode 11, a hydrogen electrode 12, and a solid electrolyte layer (proton conductor) 13 interposed between the air electrode 11 and the hydrogen electrode 12. In the proton conductive cell structure 10, the solid electrolyte layer 13 is sandwiched between the air electrode 11 and the hydrogen electrode 12, with a first main surface 14 of the solid electrolyte layer 13 in contact with the air electrode 11 and a second main surface 15 of the solid electrolyte layer 13 in contact with the hydrogen electrode 12. The hydrogen electrode 12 and the solid electrolyte layer 13 are integrated by sintering to form a composite of the hydrogen electrode 12 and the solid electrolyte layer 13.
[0027] The thickness of the solid electrolyte layer 13 is, for example, preferably 3 μm or more and 100 μm or less, and more preferably 5 μm or more and 20 μm or less. The hydrogen electrode 12 is thicker than the air electrode 11, and functions as a support for the solid electrolyte layer 13 (and thus the proton conductive cell structure 10). However, the thickness of the hydrogen electrode 12 does not necessarily have to be thicker than the air electrode 11; for example, the thickness of the hydrogen electrode 12 and the thickness of the air electrode 11 may be approximately the same.
[0028] <Solid electrolyte layer (proton conductor)> The solid electrolyte layer 13 is a layer made of a dense material and contains a predetermined metal oxide having proton conductivity. The metal oxide has a perovskite structure and is represented by the following formula (1): Ba x1 Sr x2 A 1-y M y O 3-δ (1) (In the formula, element A is at least one selected from the group consisting of Zr, Ce, and Hf, The element M is at least one selected from the group consisting of Y, Yb, Er, Ho, Tm, Gd, In, and Sc; δ is the amount of oxygen deficiency, satisfying 0.95 ≦ x1 + x2 ≦ 1.10 and 0 < y ≦ 0.5) It is a metal oxide represented by
[0029] In the above metal oxide, it is preferable that 50 at% (atomic percent) or more of element A is Zr and element M is Y in that it can provide a proton conductor with low resistance and high chemical stability. At this time, the higher the ratio of Zr in element A, the more preferable.
[0030] The solid electrolyte layer 13 contains the metal oxide represented by the above formula (1), and in its thickness direction, the composition ratio of Ba and Sr is different, and the ratio of Sr to the total amount of Ba and Sr is higher on the air electrode 11 side than on the hydrogen electrode 12 side. By inclining the ratio of Sr (and the ratio of Ba) along the thickness direction of the solid electrolyte layer 13, it becomes possible to increase the ion transport rate while keeping the resistance of the solid electrolyte layer 13 low. Therefore, in the metal oxide represented by the above formula (1), the ratio x1 of Ba and the ratio x2 of Sr are different depending on the position in the solid electrolyte layer 13. The ratio x1 of Ba is higher on the hydrogen electrode 12 side than on the air electrode 11 side to increase the proton conductivity. Also, the ratio x2 of Sr is higher on the air electrode 11 side than on the hydrogen electrode 12 side to increase the ion transport rate.
[0031] The ratio of Sr to the total amount of Ba and Sr (Sr / [Ba + Sr]: based on the number of atoms) near the surface on the air electrode 11 side of the solid electrolyte layer 13 is 0.4 or more. Thereby, a high ion transport rate in the solid electrolyte layer 13 is ensured. If the ratio of Sr on the air electrode 11 side is less than 0.4, the ion transport rate is low, and hole conduction is likely to occur in an oxygen atmosphere. The upper limit of the ratio of Sr on the air electrode 11 side is not particularly limited, and the ratio of Sr may be 1.0 or less.
[0032] The ratio of Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]: based on the number of atoms) in the vicinity of the surface of the solid electrolyte layer 13 on the hydrogen electrode 12 side is 0.003 or more and 0.3 or less. This ensures low resistance of the solid electrolyte layer 13. If the ratio of Sr on the hydrogen electrode 12 side exceeds 0.3, the resistance of the solid electrolyte layer 13 increases. Since the coexistence of a small amount of Sr with Ba improves proton conductivity, the resistance of the solid electrolyte layer 13 also increases when the ratio of Sr is less than 0.003. The ratio of Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]) in the vicinity of the surface of the solid electrolyte layer 13 on the hydrogen electrode 12 side is preferably 0.003 or more and 0.1 or less in order to reduce resistance.
[0033] In the present disclosure, the vicinity of the surface of solid electrolyte layer 13 refers to a position 0.5 μm inward from each of main surfaces 14 and 15 of solid electrolyte layer 13 in the thickness direction. The ratio of Sr to the total amount of Ba and Sr in the solid electrolyte layer 13 (Sr / [Ba+Sr]: based on the number of atoms) is calculated by observing a cross section of the solid electrolyte layer 13 with a field emission electron probe microanalyzer (FE-EPMA). Here, a normal line is drawn to the first main surface (the surface on the air electrode 11 side) 14 of the solid electrolyte layer 13, and the elemental amounts of Ba and Sr are measured at intervals of 0.1 μm along this normal line, and the ratio of Sr to the total amount of Ba and Sr is calculated from the results. The value calculated from the observation results at a position 0.5 μm inward from the main surface of solid electrolyte layer 13 in the thickness direction, or at a position closest to this position, is taken as the measurement value near the surface of solid electrolyte layer 13.
[0034] In the solid electrolyte layer 13, the ratio of Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]) at the center portion in the thickness direction is preferably 0.005 or more and 0.3 or less. In this case, the solid electrolyte layer 13 is more suitable for increasing the ion transport number while keeping the resistance low. On the other hand, when the Sr ratio (Sr / [Ba+Sr]) at the center of the solid electrolyte layer 13 in the thickness direction is less than 0.005 or exceeds 0.3, the resistance of the solid electrolyte layer 13 may become high. The central portion of solid electrolyte layer 13 in the thickness direction refers to a position equidistant from two main surfaces 14, 15 of solid electrolyte layer 13. A value calculated from the observation results at a position equidistant from two main surfaces 14, 15 of solid electrolyte layer 13 or a position closest to this position is defined as the measured value of the central portion of solid electrolyte layer 13 in the thickness direction.
[0035] It is preferable that the solid electrolyte layer 13 has an entire region of 6% of the total thickness in the thickness direction from the surface on the air electrode 11 side toward the hydrogen electrode 12 side such that the ratio of Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]) is 0.3 or more. Since the ion transport number of the solid electrolyte layer 13 tends to decrease on the air electrode 11 side, by satisfying the above-mentioned configuration, a high ion transport number can be ensured.
[0036] The proton conductor according to the present disclosure can ensure a high ionic transport number even in an oxygen atmosphere. The ionic transport number is the ratio of the amount of electricity carried by anions and cations to the total amount of electricity carried by electrons, holes, anions, and cations when a current is passed through an electrolyte. Note that the ionic transport number is 1 when the total amount of electricity carried is equal to the amount of electricity carried by anions and cations. For example, in the case of BZY or SZY, protons, oxide ions, and holes exist as carriers, so the ionic transport number indicates the ratio of the electricity flowing by protons and oxide ions to the total electricity.
[0037] <Air electrode> In the case of a fuel cell, for example, the air electrode 11 has a porous structure that can adsorb oxygen molecules and dissociate and ionize them. In the air electrode 11, a reaction between protons conducted through the solid electrolyte layer 13 and oxide ions (oxygen reduction reaction) occurs. The oxide ions are generated by dissociation of an oxidant (oxygen) introduced from the oxidant flow path.
[0038] As the material of the air electrode 11, for example, known materials used as the cathode of a fuel cell can be used. Among them, compounds containing lanthanum and having a perovskite structure (such as ferrite, manganite, cobaltite, etc.) are preferable, and among these compounds, those further containing strontium are more preferable. Specifically, for example, lanthanum strontium cobalt ferrite (LSCF: La 1-x Sr x Fe 1-y Co y O 3-δ , 0 < x < 1, 0 < y < 1), lanthanum strontium manganite (LSM: La 1-x Sr x MnO 3-δ , 0 < x < 1), lanthanum strontium cobaltite (LSC: La 1-x Sr x CoO 3-δ , 0 < x < 1), etc. Here, δ indicates the amount of oxygen deficiency.
[0039] The air electrode 11 can be formed, for example, by sintering the above materials. The air electrode 11 may contain a catalyst such as Pt from the viewpoint of promoting the reaction between protons and oxide ions. When containing a catalyst, the air electrode 11 can be formed by mixing the catalyst and the above material and sintering them. At this time, a binder, an additive, a dispersion medium, etc. may be used together with the material of the air electrode 11 as necessary. The thickness of the air electrode 11 is not particularly limited, but it may be about 5 μm to 40 μm.
[0040] Further, when the proton-conducting cell structure 10 is a steam electrolysis cell, for example, a composite of Ni and yttrium-stabilized zirconia can be used as the material of the air electrode 11.
[0041] <Hydrogen electrode> The hydrogen electrode 12 has a porous structure. In the case of a fuel cell, for example, the hydrogen electrode 12 undergoes a reaction (oxidation reaction of the fuel) in which a fuel such as hydrogen is oxidized to release protons and electrons.
[0042] The material of the hydrogen electrode 12 may be, for example, a material used as an anode in a fuel cell. Specifically, a composite of nickel or a nickel compound (nickel oxide, etc.), which is a catalyst component, and a proton conductor can be used. The nickel compound is reduced during use of the cell structure to produce Ni. The proton conductor is a metal oxide represented by the formula (2) described below.
[0043] The hydrogen electrode 12 can be formed, for example, by mixing NiO powder with a powder of a metal oxide represented by the formula (2) described below, and sintering the mixture. The thickness of the hydrogen electrode 12 may be, for example, 10 μm to 2 mm, or may be 10 μm to 100 μm. The hydrogen electrode 12 may be thickened to function as a support for supporting the solid electrolyte layer 13. In this case, the thickness of the hydrogen electrode 12 may be set to, for example, 100 μm to 2 mm.
[0044] When the proton conductive cell structure 10 is a steam electrolysis cell, the hydrogen electrode 12 may be made of a conductive oxide that is stable in an oxidizing atmosphere, such as lanthanum manganese oxide doped with strontium.
[0045] [Electrochemical Devices] The proton conductive cell structure 10 can be used as a component of an electrochemical device. Examples of the electrochemical device include a fuel cell, a steam electrolysis cell, and a gas decomposition device.
[0046] <Fuel cell> The fuel cell may include the proton conductive cell structure 10, and may have the same configuration as a conventional fuel cell. Specifically, for example, a separator having an oxidant flow path formed therein for supplying an oxidant to the air electrode 11 via a current collector is provided on the air electrode 11 side of the proton conductive cell structure 10, and a separator having a fuel flow path formed therein for supplying a fuel to the hydrogen electrode 12 via a current collector is provided on the hydrogen electrode 12 side of the proton conductive cell structure 10. The fuel cell according to the present disclosure includes the proton conductive cell structure 10, and therefore can achieve both high output and a high ion transport number. The above fuel cell can be manufactured by a known method, except for using the proton conductive cell structure 10.
[0047] <Steam electrolysis cell> The steam electrolysis cell may be any cell as long as it includes the proton conductive cell structure 10, and other components may be known. Furthermore, the steam electrolysis cell may be manufactured by a known method, except for the use of the proton conductive cell structure 10.
[0048] <Gas decomposition equipment> The gas decomposition device may be any device that includes the proton conductive cell structure 10. When gases including ammonia, methane, propane, etc. are introduced into the hydrogen electrode 12 of the proton conductive cell structure 10, decomposition reactions of these gases occur at the hydrogen electrode 12, generating hydrogen. Therefore, the proton conductive cell structure 10 can be used in a gas decomposition device. For example, hydrogen generated by the decomposition of ammonia is oxidized by the hydrogen electrode 12 to generate protons. The generated protons pass through the solid electrolyte layer 13 and move to the oxygen electrode 11. Meanwhile, N 2 is emitted as exhaust gas. In the gas decomposition device, a catalyst capable of decomposing the gas may be included in the hydrogen electrode 12. Examples of the catalyst capable of decomposing gases such as ammonia include compounds containing at least one catalytic component selected from the group consisting of Fe, Co, Ti, Mo, W, Mn, Ru, and Cu.
[0049] [Method of manufacturing proton conductive cell structure] The proton conductive cell structure 10 is (1) a step of preparing an air electrode material, a solid electrolyte material A, a solid electrolyte material B, and a hydrogen electrode material (first step); (2) a step (second step) of laminating a layer containing a hydrogen electrode material and a layer containing a solid electrolyte material A, and then heating the resulting laminate to form a composite in which the hydrogen electrode 12 and the solid electrolyte precursor layer are integrated together; (3) contacting a solid electrolyte material B with the surface of the solid electrolyte precursor layer opposite to the hydrogen electrode 12 side and heating the surface in this state to form a composite of the hydrogen electrode 12 and the solid electrolyte layer 13 (third step); (4) a step (fourth step) of laminating a layer containing a material for an air electrode on a surface (the surface opposite to the hydrogen electrode) of the solid electrolyte layer 13, and then heating the resulting laminate to form the air electrode 11; The composition can be produced by a method comprising the steps of:
[0050] (1st step) A material for an air electrode, a material A for a solid electrolyte, a material B for a solid electrolyte, and a material for a hydrogen electrode are prepared. Here, the hydrogen electrode material is a nickel compound having a perovskite structure and represented by the following formula (2): Ba x1 A 1-y M y O 3-δ (2) (In the formula, element A is at least one selected from the group consisting of Zr, Ce, and Hf, The element M is at least one selected from the group consisting of Y, Yb, Er, Ho, Tm, Gd, In, and Sc; δ is the amount of oxygen deficiency, satisfying 0.95 ≦ x1 ≦ 1.10, 0 < y ≦ 0.5) Prepare a mixture with the metal oxide represented by . The material for the hydrogen electrode is preferably a mixture of NiO powder and the powder of the metal oxide represented by the above formula (2). The composition of the metal oxide represented by the above formula (2) is preferably the same as that of the metal oxide represented by the above formula (2) contained in the solid electrolyte material A.
[0051] As the solid electrolyte material A, prepare a paste or slurry in which the powder of the metal oxide represented by the above formula (2) is mixed with a binder and a dispersion medium. Examples of the binder include known materials used in the production of ceramic materials, such as polymer binders, waxes, etc., but are not particularly limited. Examples of the polymer binder include cellulose derivatives, vinyl acetate resins, acrylic resins, etc. Examples of the cellulose derivative include ethyl cellulose, cellulose ether, etc. The concept of the vinyl acetate resin also includes saponified products of vinyl acetate resins such as polyvinyl alcohol. Examples of the wax include paraffin wax, etc. The amount of the binder is not particularly limited, and for example, it may be 1 part by mass to 20 parts by mass, preferably 1.5 parts by mass to 15 parts by mass, based on 100 parts by mass of the powder of the metal oxide represented by the above formula (2).
[0052] Examples of the dispersion medium include water, organic solvents, etc., but are not particularly limited. Examples of the organic solvent include hydrocarbons such as toluene; alcohols such as ethanol, isopropanol; carbitols such as butyl carbitol acetate, etc. The amount of the dispersion medium is not particularly limited, and for example, it may be 50 parts by mass to 200 parts by mass, based on 100 parts by mass of the powder of the metal oxide represented by the above formula (2). The solid electrolyte material A may contain various additives such as surfactants and peptizing agents as required. In the above-described material A for solid electrolyte, the composition of the metal oxide represented by the above formula (2) may be appropriately determined in consideration of the constituent elements and composition ratios of the solid electrolyte layer to be formed.
[0053] As the above-described material B for solid electrolyte, a material having a perovskite-type structure and represented by the following formula (3): Sr x2 A 1-y M y O 3-δ (3) (In the formula, element A is at least one selected from the group consisting of Zr, Ce, and Hf, element M is at least one selected from the group consisting of Y, Yb, Er, Ho, Tm, Gd, In, and Sc, δ is the amount of oxygen deficiency, satisfying 0.95 ≦ x2 ≦ 1.10 and 0 < y ≦ 0.5) A mixture of a powder of a metal oxide represented by the formula and a powder of a strontium compound (Sr compound) such as SrCO 3 is prepared. In the above-described material B for solid electrolyte, the composition of the metal oxide represented by the above formula (3) may be appropriately determined in consideration of the constituent elements and composition ratios of the solid electrolyte layer to be formed. In the above-described material B for solid electrolyte, the mixing ratio of the powder of the metal oxide represented by the above formula (3) and the powder of an Sr compound such as SrCO 3 is preferably 99:1 to 70:30, on a mass basis, of metal oxide:Sr compound. If the ratio of the Sr compound is too small, Sr may not diffuse sufficiently into the solid electrolyte precursor layer. On the other hand, if the ratio of the Sr compound is too large, in the metal oxide represented by formula (1) constituting the solid electrolyte layer, x1 + x2 is likely to be > 1.1, and the chemical stability may be lowered.
[0054] As the above-described material for air electrode, a paste or slurry in which powders of LSCF or LSM, which are materials for air electrodes, and a binder and a dispersion medium are mixed is prepared. Here, as each of the binder and the dispersion medium, those similar to those used for the material A for solid electrolyte can be mentioned. The amounts of the binder and the dispersion medium are not particularly limited, and may be appropriately selected so as to be suitable for coating the air electrode material.
[0055] (2nd process) In the second step, a layer containing the hydrogen electrode material and a layer containing the solid electrolyte material A are laminated and heated at 1300 to 1700° C. for main sintering to form a composite of the hydrogen electrode 12 and the solid electrolyte precursor layer. In this step, the hydrogen electrode material and the solid electrolyte material A are co-sintered to form a composite.
[0056] Here, the method of forming each layer is not particularly limited, and the layer containing the hydrogen electrode material may be formed, for example, by press molding such as uniaxial molding. The layer containing the hydrogen electrode material may be pre-fired after molding and before laminating the layer containing the solid electrolyte material A. The pre-fired may be performed at a temperature (e.g., 900°C to 1100°C) lower than the temperature at which the hydrogen electrode material is sintered. Pre-fired makes it easier to apply the solid electrolyte material A.
[0057] The layer containing the solid electrolyte material A may be formed by applying a paste or slurry of the solid electrolyte material A to the surface of the layer containing the hydrogen electrode material by screen printing, spray coating, spin coating, dip coating, or the like. In this step, after the layer containing the solid electrolyte material A is formed, a binder removal treatment for removing resin components such as binders may be carried out before the main firing. The binder removal process may be carried out, for example, by heating at about 500° C. to 800° C. in the atmosphere. In this step, the hydrogen electrode 12 and the solid electrolyte precursor layer are integrated together to form a composite body of the hydrogen electrode and the solid electrolyte precursor layer.
[0058] (3rd step) In the third step, solid electrolyte material B is brought into contact with the surface of the solid electrolyte precursor layer of the above composite opposite to the hydrogen electrode 12 side, and heated in this state to form a composite of the hydrogen electrode 12 and the solid electrolyte layer 13. Specifically, the above composite is placed on a plate made of MgO or the like with the solid electrolyte precursor layer facing up, and solid electrolyte material B (powder mixture) is poured on top of it so that the above composite is embedded in solid electrolyte material B. Thereafter, in this state, a heat treatment is performed at 1200° C. to 1400° C. for 0 to 5 hours. In this way, a hydrogen electrode-solid electrolyte layer composite in which the hydrogen electrode 12 and the solid electrolyte layer 13 are integrated can be produced. The method for producing such a composite is also a method for producing a proton conductor according to the present disclosure.
[0059] (4th step) In the fourth step, a layer containing a material for the air electrode is laminated on the surface of the solid electrolyte layer 13 of the hydrogen electrode-solid electrolyte layer composite, and sintered by heating at, for example, 800° C. to 1100° C. to form the air electrode 2. The layer containing the air electrode material may be formed by applying a paste or slurry of the air electrode material to the surface of the solid electrolyte layer 13 by screen printing, spray coating, spin coating, dip coating, or the like. In this step, after the layer containing the air electrode material is formed, a binder removal treatment may be carried out before firing to remove resin components such as binders. The binder removal process may be carried out, for example, by heating at about 500° C. to 800° C. in the atmosphere. By carrying out these first to fourth steps, the proton conductor cell structure 10 can be manufactured. Furthermore, after the third step and / or the fourth step, the side surface of the solid electrolyte layer may be subjected to cutting, grinding, or the like, if necessary.
[0060] Second embodiment [Proton-conducting cell structure] FIG. 2 is a diagram illustrating a schematic diagram of an example of a proton conductive cell structure according to the present disclosure. The proton conductive cell structure 20 of this embodiment includes an air electrode 21, a hydrogen electrode 22, and a solid electrolyte layer (proton conductor) 23 interposed between the air electrode 21 and the hydrogen electrode 22. The solid electrolyte layer 23 is composed of a first solid electrolyte layer 23A made of a dense material provided on the hydrogen electrode 22 side, and a second solid electrolyte layer 23B made of a porous material provided on the air electrode 21 side. A proton conductive cell structure 20 of this embodiment differs from the proton conductive cell structure 10 of the first embodiment in the configuration of a solid electrolyte layer 23.
[0061] The solid electrolyte layer 23 has a two-layer structure, with a main surface 24 of the second solid electrolyte layer 23B opposite to the first solid electrolyte layer 23A side being in contact with the air electrode 21, and a main surface 25 of the first solid electrolyte layer 23A opposite to the second solid electrolyte layer 23B side being in contact with the hydrogen electrode 22. The hydrogen electrode 22 and the solid electrolyte layer 23 are integrated by sintering to form a composite of the hydrogen electrode 22 and the solid electrolyte layer 23. The thickness of the first solid electrolyte layer 23A is, for example, preferably not less than 3 μm and not more than 100 μm, and more preferably not less than 5 μm and not more than 20 μm. The thickness of second solid electrolyte layer 23B is, for example, preferably not less than 3 μm and not more than 30 μm, and more preferably not less than 3 μm and not more than 15 μm. The total thickness of the solid electrolyte layer 23 is preferably, for example, not less than 6 μm and not more than 35 μm.
[0062] <Solid electrolyte layer (proton conductor)> The first solid electrolyte layer 23A is a dense layer containing a predetermined metal oxide having proton conductivity. The first solid electrolyte layer 23A may have a configuration similar to that of the solid electrolyte layer 13 in the first embodiment. Moreover, the preferred configuration of first solid electrolyte layer 23A is similar to the preferred configuration of solid electrolyte layer 13 in the first embodiment.
[0063] The second solid electrolyte layer 23B is a porous layer, It has a perovskite structure and the following formula (1): Ba x1 Sr x2 A 1-y M y O 3-δ (1) (In the formula, element A is at least one selected from the group consisting of Zr, Ce, and Hf, element M is at least one selected from the group consisting of Y, Yb, Er, Ho, Tm, Gd, In, and Sc, δ is the amount of oxygen deficiency, satisfying 0.95 ≦ x1 + x2 ≦ 1.10 and 0 < y ≦ 0.5) and contains a metal oxide represented by
[0064] In this embodiment, the solid electrolyte layer 23 has, in addition to the first solid electrolyte layer 23A, a second solid electrolyte layer 23B made of a porous material. Therefore, in the solid electrolyte layer 23 (particularly, the second solid electrolyte layer 23B), the three-phase interface of the air electrode material, air, and electrolyte increases, the electrode activity is improved, and the ion transport rate becomes even better. The porosity of the second solid electrolyte layer 23B is preferably 6 to 40% from the viewpoints of increasing the three-phase interface of the air electrode material, air, and electrolyte and reducing the resistance.
[0065] In the embodiment of the present disclosure, whether the solid electrolyte layer is porous or dense is determined by microscopic observation of a cross-section obtained by cutting the solid electrolyte layer along the thickness direction. Specifically, the obtained microscopic image is divided into voids and non-voids by binarization processing, the ratio of the total area of the voids to the total area of the sum of the total area of the voids and the total area of the non-voids is calculated as the porosity, and the determination is made based on the obtained porosity. In the embodiment of the present disclosure, a layer having a porosity of 5% or less is defined as a dense layer, and a layer having a porosity exceeding 5% is defined as a porous layer.
[0066] In the metal oxide contained in the second solid electrolyte layer 23B, in the above formula (1), it is preferable that 50 at% or more of element A is Zr and element M is Y. By making more than half of element A be Zr, the chemical stability can be enhanced. By making element M be Y, the proton conductivity can be enhanced. At this time, the higher the ratio occupied by Zr in element A, the more preferable. In addition, in the metal oxide contained in second solid electrolyte layer 23B, in the above formula (1), x1 is preferably 0≦x1≦0.6, and x2 is preferably 0.4≦x2≦1.0. Second solid electrolyte layer 23B may have the same composition throughout, or Ba ratio x1 and Sr ratio x2 may differ depending on the position within second solid electrolyte layer 23B.
[0067] <Air pole / hydrogen pole> The configurations of the air electrode 21 and the hydrogen electrode 22 are similar to those of the air electrode 11 and the hydrogen electrode 12 in the first embodiment.
[0068] [Electrochemical Devices] The proton conductive cell structure 20, like the proton conductive cell structure 10 of the first embodiment, can be used as a constituent member of electrochemical devices such as fuel cells, steam electrolysis cells, and gas decomposition devices.
[0069] [Method of manufacturing proton conductive cell structure] The proton conductive cell structure 20 is (1) a step of preparing an air electrode material, a solid electrolyte material A, a solid electrolyte material C, and a hydrogen electrode material (first step); (2) a step (second step) of laminating a layer containing a hydrogen electrode material and a layer containing a solid electrolyte material A, and then heating the resulting laminate to form a composite in which the hydrogen electrode 22 and the solid electrolyte precursor layer are integrated together; (3) applying a solid electrolyte material C to the surface of the solid electrolyte precursor layer opposite to the hydrogen electrode 12 side, and heating the solid electrolyte material C in this state to form a composite of the hydrogen electrode 12 and the solid electrolyte layer 23 having the dense first solid electrolyte layer 23A and the porous second solid electrolyte layer 23B (third step); (4) a step (fourth step) of laminating a layer containing a material for an air electrode on a surface (surface opposite to the hydrogen electrode) of the solid electrolyte layer 23 (second solid electrolyte layer 23B) and then heating the resulting laminate to form the air electrode 21; The composition can be produced by a method comprising the steps of:
[0070] (1st step) Prepare an air electrode material, a solid electrolyte material A, a solid electrolyte material C, and a hydrogen electrode material. The air electrode material, the solid electrolyte material A, and the hydrogen electrode material are prepared in the same manner as in the first embodiment.
[0071] As the solid electrolyte material C, it has a perovskite structure and the following formula (3): Sr x2 A 1-y M y O 3-δ (3) (In the formula, element A is at least one selected from the group consisting of Zr, Ce, and Hf, element M is at least one selected from the group consisting of Y, Yb, Er, Ho, Tm, Gd, In, and Sc, δ is the oxygen deficiency amount, satisfying 0.95 ≦ x2 ≦ 1.10 and 0 < y ≦ 0.5) Prepare a paste or slurry obtained by mixing a powder of a metal oxide represented by the formula, a powder of a strontium compound (Sr compound) such as SrCO 3 and a binder and a dispersion medium. In the solid electrolyte material C, the composition of the metal oxide represented by the formula (3) may be appropriately determined in consideration of the constituent elements and composition ratio of the solid electrolyte layer to be formed. In the solid electrolyte material C, the mixing ratio of the powder of the metal oxide represented by the formula (3) and the powder of the Sr compound such as SrCO 3 is preferably 99:1 to 75:25, metal oxide:Sr compound, on a mass basis. If the ratio of the Sr compound is too small, Sr may not diffuse sufficiently into the solid electrolyte precursor layer. On the other hand, if the ratio of the Sr compound is too large, in the metal oxide represented by the formula (1) constituting the solid electrolyte layer B, x1 + x2 is likely to be > 1.1, resulting in low chemical stability.
[0072] The binder may be any known material used in the manufacture of ceramic materials, such as, but not limited to, polymer binders and waxes. The polymer binder may be, for example, a cellulose derivative, a vinyl acetate resin, or an acrylic resin. The cellulose derivative may be, for example, ethyl cellulose or cellulose ether. The concept of vinyl acetate resin includes saponified vinyl acetate resins such as propyl alcohol. The wax may be, for example, paraffin wax. The amount of the binder is not particularly limited, and may be, for example, 1 to 20 parts by mass, preferably 1.5 to 15 parts by mass, per 100 parts by mass of the total amount of the powder of the metal oxide represented by the above formula (3) and the powder of the Sr compound.
[0073] The dispersion medium is not particularly limited, but may be, for example, water, an organic solvent, etc. Examples of the organic solvent include hydrocarbons such as toluene, alcohols such as ethanol and isopropanol, and carbitols such as butyl carbitol acetate. The amount of the dispersion medium is not particularly limited, and may be, for example, 50 to 150 parts by mass per 100 parts by mass of the total amount of the powder of the metal oxide represented by the formula (3) and the powder of the Sr compound. The solid electrolyte material C may further contain various additives such as a surfactant and a deflocculating agent, if necessary.
[0074] (2nd process) In the second step, a layer containing the hydrogen electrode material and a layer containing the solid electrolyte material A are laminated and heated at 1300 to 1700° C. for main sintering to form a composite of the hydrogen electrode 12 and the solid electrolyte precursor layer. This step may be performed in the same manner as the second step in the first embodiment.
[0075] (3rd step) In the third step, a paste of solid electrolyte material C is applied to the surface of the solid electrolyte precursor layer of the above composite opposite to the hydrogen electrode 12 side, and heated in this state to form a composite of the hydrogen electrode 22 and the solid electrolyte layer 23. Specifically, a paste of the solid electrolyte material C is applied to the surface of the solid electrolyte precursor layer (the surface opposite to the hydrogen electrode 22 side) by a method such as screen printing, spray coating, spin coating, or dip coating. Thereafter, in this state, a heat treatment is performed at 1200° C. to 1400° C. for 0 to 5 hours. In this way, a hydrogen electrode-solid electrolyte layer composite in which the hydrogen electrode 22 and the solid electrolyte layer 23 are integrated can be produced.
[0076] Furthermore, by employing the technique of this step, it is possible to form solid electrolyte layer 23 having a two-layer structure including first solid electrolyte layer 23A made of a dense material and second solid electrolyte layer 23B made of a porous material. The method for producing such a composite is also a method for producing a proton conductor according to the present disclosure.
[0077] (4th step) In the fourth step, a layer containing a material for the air electrode is laminated on the surface of the solid electrolyte layer 23 of the hydrogen electrode-solid electrolyte layer composite, and sintered by heating at, for example, 800° C. to 1100° C. to form the air electrode 21. This step may be performed in the same manner as the fourth step in the first embodiment. By carrying out these first to fourth steps, the proton conductor cell structure 20 can be manufactured. Furthermore, after the third step and / or the fourth step, the side surface of the solid electrolyte layer may be subjected to cutting, grinding, or the like, if necessary.
[0078] (Other embodiments) Although the proton conductive cell structures of the first and second embodiments are laminated, the shape of the cell structure according to the present disclosure is not limited to this. For example, the cell structure may be cylindrical, rolled with the hydrogen electrode facing inward, so as to have a hollow space. When the proton conductive cell structure has a laminated shape, each layer may have a rectangular plate shape or a disk shape. EXAMPLES
[0079] Next, the present invention will be described in more detail based on examples, but the present invention is not limited to these examples.
[0080] <BaZr 0.8 Y 0.2 O 2.9 Powder preparation> Barium carbonate, zirconium oxide, and yttrium oxide were mixed in a ball mill for 24 hours in a molar ratio such that the ratio of Ba was 1.0 and the ratio of Y was 0.2, and a mixture was obtained. The mixture obtained was pre-fired at 1000°C for 10 hours. The pre-fired mixture was processed in a ball mill for 10 hours, uniaxially molded, and then fired at 1300°C for 10 hours in an air atmosphere. The fired sample was pulverized in a mortar and then processed in a ball mill for 10 hours. The obtained powder was again uniaxially molded, fired at 1300°C for 10 hours, and then processed in a ball mill for 10 hours to obtain BaZr 0.8 Y 0.2 O 2.9 A powder (hereinafter, also referred to as BZY20 powder) was obtained.
[0081] <SrZr 0.85 Y 0.15 O 2.975 Powder preparation> Strontium carbonate, zirconium oxide, and yttrium oxide were mixed in a ball mill for 24 hours in a molar ratio such that the ratio of Sr was 1.0 and the ratio of Y was 0.15, and the mixture was obtained. The obtained mixture was pre-fired at 1000°C for 10 hours. The pre-fired mixture was processed in a ball mill for 10 hours, uniaxially molded, and then fired at 1300°C for 10 hours in an air atmosphere. The fired sample was pulverized in a mortar and then processed in a ball mill for 10 hours. The obtained powder was again uniaxially molded, fired at 1300°C for 10 hours, and then processed in a ball mill for 10 hours to obtain SrZr 0.85 Y0.15 O 2.975 A powder (hereinafter also referred to as SZY15 powder) was obtained.
[0082] <Example 1> (1) NiO and BZY20 powder were mixed in a ratio of 7:3 (mass ratio), ball milled, and then uniaxially molded. The resulting molded body was calcined at 1000°C, and a BZY20 paste, which was a mixture of 100 parts by mass of BZY20 powder, 125 parts by mass of an organic solvent (butyl carbitol acetate (BCA)), and 5 parts by mass of a binder (ethyl cellulose), was laminated on the calcined molded body by screen printing. The obtained laminate was heated at 750° C. to remove the binder, and then co-sintered at 1450° C. to form a sintered body.
[0083] (2) The sintered body obtained was placed on a MgO plate with the side with the BZY20 paste laminated facing up, and then SZY15 powder and SrCO 3 The sintered body was buried in the powder, and in this state, heat treatment was performed in a heating furnace at 1300°C for 0 hours. Here, heat treatment at 1300°C for 0 hours refers to a heat treatment in which the temperature in the furnace is raised from 20°C to 1300°C over 6 hours and 40 minutes, and immediately after reaching 1300°C, the temperature is lowered from 1300°C to 20°C over 6 hours and 40 minutes (heat treatment pattern 1). Through these steps, a hydrogen electrode-solid electrolyte layer composite A was produced in which a disk-shaped hydrogen electrode and a solid electrolyte layer were integrated together. The thickness of the solid electrolyte layer formed in this example is 15 μm.
[0084] <Example 2> First, a sintered body was formed in the same manner as in step (1) of Example 1. Then, the sintered body was placed on a MgO plate with the BZY20 paste layered side facing up, and the SZY15 powder and SrCO 3The sintered body was buried in the powder, and in this state, heat-treated in a heating furnace at 1300°C for 2 hours. Here, heat treatment at 1300°C for 2 hours refers to a heat treatment in which the temperature in the furnace is raised from 20°C to 1300°C over 6 hours and 40 minutes, then maintained at 1300°C for 2 hours, and then cooled from 1300°C to 20°C over 6 hours and 40 minutes (heat treatment pattern 2). Through the above-mentioned heat treatment, a hydrogen electrode-solid electrolyte layer composite B was produced. The thickness of the solid electrolyte layer formed in this example is 14 μm.
[0085] <Example 3> First, a sintered body was formed in the same manner as in step (1) of Example 1. Then, the sintered body was placed on a MgO plate with the BZY20 paste layered side facing up, and the SZY15 powder and SrCO 3 The sintered body was buried in the powder, and in this state, heat treatment was performed in a heating furnace at 1400°C for 2 hours. Here, heat treatment at 1400°C for 2 hours refers to a heat treatment in which the temperature in the furnace is raised from 20°C to 1400°C over 7 hours and 27 minutes, then the temperature in the furnace is maintained at 1400°C for 2 hours, and then the temperature is lowered from 1400°C to 20°C over 7 hours and 27 minutes (heat treatment pattern 3). Through the above-mentioned heat treatment, a hydrogen electrode-solid electrolyte layer composite C was produced. The thickness of the solid electrolyte layer formed in this example is 17 μm.
[0086] <Example 4> First, a sintered body was formed in the same manner as in step (1) of Example 1. Next, SZY15 powder and SrCO 3 The powders were mixed in a ratio of 9:1 (by mass) to obtain SZY15 powder and SrCO 3A paste made by mixing 5 parts by weight of a binder (ethyl cellulose) and 130 parts by weight of an organic solvent (butyl carbitol acetate (BCA)) with respect to a total amount of 100 parts by weight of the powder was laminated by screen printing. After that, a heat treatment was performed in a heating furnace at 1300°C for 0 hours (heat treatment pattern 1). Through such heat treatment, a hydrogen electrode-solid electrolyte layer composite D was produced. Regarding the thickness of the solid electrolyte layers formed in this example, the first solid electrolyte layer made of a dense material is 14 μm thick, and the second solid electrolyte layer made of a porous material is 10 μm thick. The porosity of the first solid electrolyte layer was 0%, and the porosity of the second solid electrolyte layer was 8%.
[0087] <Comparative Example 1> A sintered body prepared in the same manner as in step (1) of Example 1 was used as hydrogen electrode-solid electrolyte layer composite E of this comparative example. The thickness of the solid electrolyte layer formed in this comparative example was 16 μm.
[0088] <Comparative Example 2> NiO and SZY15 powder were mixed in a mass ratio of 7:3, ball milled, and then uniaxially molded. The resulting molded body was calcined at 1000°C, and an SZY15 paste was laminated on the calcined molded body by screen printing, the paste being a mixture of 100 parts by mass of SZY15 powder, 140 parts by mass of an organic solvent (butyl carbitol acetate (BCA)), and 5 parts by mass of a binder (ethyl cellulose). The obtained laminate was heated at 750° C. to remove the binder, and then co-sintered at 1450° C. to form a sintered body. This sintered body was designated as hydrogen electrode-solid electrolyte layer composite F of this comparative example. The thickness of the solid electrolyte layer formed in this comparative example was 15 μm.
[0089] <Comparative Example 3> NiO and BZY20 powder were mixed in a mass ratio of 7:3, ball milled, and then uniaxially molded. The resulting molded body was calcined at 1000° C., and the same SZY15 paste as in Comparative Example 2 was laminated on the calcined molded body by screen printing. The obtained laminate was heated at 750° C. to remove the binder, and then co-sintered at 1450° C. to form a sintered body. This sintered body was designated as hydrogen electrode-solid electrolyte layer composite G of this comparative example. The thickness of the solid electrolyte layer formed in this comparative example was 15 μm.
[0090] <Comparative Example 4> First, a sintered body was formed in the same manner as in step (1) of Example 1. Thereafter, a 500 nm SZY15 film was laminated by pulsed laser deposition (PLD) on the side of the obtained sintered body on which the BZY20 paste was laminated. Through this process of forming the SZY15 membrane, a hydrogen electrode-solid electrolyte layer composite H was produced. The thickness of the solid electrolyte layer formed in this comparative example was 15.5 μm.
[0091] <Cross-section observation / composition analysis> Regarding the composition of the solid electrolyte layer in the hydrogen electrode-solid electrolyte layer composites produced in Examples 1 to 4 and Comparative Examples 3 and 4, the cross section of the solid electrolyte layer was observed and measured by a field emission electron probe microanalyzer (FE-EPMA), and the element ratios of the solid electrolyte layer, "Ba / (Ba+Sr): based on the number of atoms" and "Sr / (Ba+Sr): based on the number of atoms", were calculated. The results are shown in Table 1 and Figs. 3A, 3B, 4A, 4B, 5, 6, 7, and 8. In the graphs of Figs. 3A to 8, the horizontal axis indicates the position in the thickness direction of the cross section of the solid electrolyte layer, and the vertical axis indicates the above element ratios of the solid electrolyte layer. Here, the solid electrolyte layer as the observation sample was embedded in resin, polished, and then carbon was evaporated onto the entire sample, after which the cross section was processed using a JEOL cross section polisher (SM-09010). The EPMA used was the JEOL JXA-8530F. Acceleration voltage: 15 kV Irradiation current: 100nA Sampling time: 1s Probe diameter: 0.1μmφ Sample feed step: 0.1μm The measurement was carried out under the following conditions. The quantitative analysis was carried out by the ZAF method, and BaF was used as the standard sample for Ba. 2 The standard sample of Sr is SrTiO 3 (Both standard samples manufactured by JEOL were used.)
[0092] [Table 1]
[0093] As shown in Table 1 and FIGS. 3A to 8, in the hydrogen electrode-solid electrolyte layer composites A to D produced in Examples 1 to 4, Sr / (Ba+Sr) was 0.4 or more near the surface of the first solid electrolyte layer on the side opposite the hydrogen electrode (also referred to as the air electrode side), and a composition gradient of Ba and Sr was formed in the solid electrolyte layer. The porosity of the solid electrolyte layer in Examples 1 to 3 was 0%, while the solid electrolyte layer in Example 4 had a region with a porosity of 8% in a 10 μm region on the side opposite the hydrogen electrode side (air electrode side). On the other hand, in the hydrogen electrode-solid electrolyte layer composite G produced in Comparative Example 3, diffusion of Sr progressed within the electrolyte layer, and the Sr composition gradient was gentle. Sr / (Ba+Sr) was about 0.4 on the side of the solid electrolyte layer opposite the hydrogen electrode (the air electrode side), Sr / (Ba+Sr) was about 0.3 on the hydrogen electrode side of the solid electrolyte layer, and Sr / (Ba+Sr) was about 0.3 to 0.4 throughout the entire solid electrolyte layer. In the hydrogen electrode-solid electrolyte layer composite H produced in Comparative Example 4, Sr was not detected in a region of the solid electrolyte layer that was more than 1.0 μm away from the side opposite the hydrogen electrode.
[0094] <Electrochemical measurements and evaluation> Fuel cells were produced using the hydrogen electrode-solid electrolyte layer composites A to H produced in the examples and comparative examples, and electrochemical measurements were carried out using the resulting fuel cells. (1) Fuel cell construction LSCF(La 0.6 Sr 0.4 Fe 0.8 Co 0.2 O 3-δ An LSCF paste was prepared by mixing powder of sucrose, a solvent (butyl carbitol acetate), and a binder (ethyl cellulose). This LSCF paste was applied by screen printing to the surface of the solid electrolyte layer of the hydrogen electrode-solid electrolyte layer composite. The LSCF was then sintered by heat treatment at 1000°C for 2 hours to form a 10 μm-thick cathode (air electrode), and a cell structure was obtained. A platinum mesh with a lead wire welded thereto was attached to the surface of each of the air electrode and hydrogen electrode of the resulting cell structure (φ16 mm) using platinum electrode paste. The ends of the lead wires opposite to the cell structure side were connected to a measuring instrument so that the current and voltage values between the lead wires could be measured.
[0095] (2) Power density measurement The operating temperature was set at 600°C, and 100 cm of hydrogen was injected as fuel gas into the hydrogen electrode of the fuel cell. 3 / min, and 200 cm of air was supplied to the air electrode. 3 The current density was changed and the maximum output density was calculated from the current density and voltage. The results are shown in Table 2.
[0096] (3) Measurement of DC resistance change DC resistance in open circuit state R OCV and DC resistance R when a voltage of OCV-0.2V is applied. 0.2 Ratio to OCV / R 0.2 was calculated as an index of the ionic transport number. The DC resistance of each was measured by electrochemical impedance spectroscopy, and the open circuit voltage (OCV) was also obtained. The measurement equipment used was a Solartron 1260A Impedance / Gain-phase Analyzer and a potentiostat 1287A. The amplitude of ±10 mV was set to 10 V for OCV or OCV-0.2 V. 6 A Nyquist diagram was obtained by plotting the real part of the frequency response of the current value when sweeping from 0.1 Hz to 0.1 Hz on the horizontal axis and the imaginary part on the vertical axis, and the intersection with the horizontal axis was read as the DC resistance. The results are shown in Table 2.
[0097] In this evaluation, "R OCV / R 0.2 " is used as an index of the ion transport number. The reasons are as follows. The equivalent circuit of the proton conductive cell structure assuming hole conduction can be shown in FIG. 9. In FIG. 9, R H is the resistance of proton conduction, R h is the resistance of hole conduction, R c is the resistance of the air electrode (cathode), R a is the resistance of the hydrogen electrode (anode), and R is the total resistance. Here, the conductivity σ and ion transport number t of the proton conductor are respectively
number
number
[0098] According to non-patent literature: T. Onishi and T. Uda, Electrochemistry, 87(3), 162-174 (2019), the higher the voltage applied to the cell structure, the higher the hole conductivity of the cell structure, and therefore the hole conductivity is smaller when the voltage is shifted to the power generation side than in the open circuit state. Based on the disclosure of this literature, the hole conductivity in the OCV-0.2V state is about 1 / 5 of the hole conductivity in the open circuit state. Therefore, the resistance of hole conduction in the OCV-0.2V state is about 5 times the resistance of hole conduction in the OCV state. Here, the DC resistance in the OCV state is R OCV The DC resistance at OCV-0.2V is R 0.2 year,
[0099]
number
number
[0100]
number
[0101] [Table 2]
[0102] The fuel cells in which the hydrogen electrode-solid electrolyte layer composites of Examples 1 to 4 were evaluated had higher transport number indices than the fuel cells in which the hydrogen electrode-solid electrolyte layer composites of Comparative Examples 1, 3, and 4 were evaluated, and the electrochemical device according to the present disclosure had good ion transport number while maintaining a high power density. On the other hand, in the fuel cells in which the hydrogen electrode-solid electrolyte layer composites of Comparative Examples 1, 3 and 4 were evaluated, it was difficult to increase the ion transport number. The fuel cell in which the hydrogen electrode-solid electrolyte layer composite of Comparative Example 2 was evaluated had a high transport number index but an extremely low output density. From these findings, it has become clear that according to the present disclosure, both a high ion transport number and high output can be achieved. [Explanation of symbols]
[0103] 10, 20 cell structure 11, 21 Air electrode 12, 22 Hydrogen electrode 13, 23 Solid electrolyte layer 14, 24 (first) main surface 15, 25 (second) main surface 23A 1st solid electrolyte layer 23B 2nd solid electrolyte layer
Claims
1. A cell structure including an air electrode, a hydrogen electrode, and a solid electrolyte layer interposed between the air electrode and the hydrogen electrode, the solid electrolyte layer includes at least a first solid electrolyte layer made of a dense material, The first solid electrolyte layer is It has a perovskite structure and the following formula (1): Ba x1 Sr x2 A 1-y M y O 3-δ (1) (In the formula, element A is at least one selected from the group consisting of Zr, Ce, and Hf, The element M is at least one selected from the group consisting of Y, Yb, Er, Ho, Tm, Gd, In, and Sc; δ is the amount of oxygen deficiency, and satisfies 0.95≦x1+x2≦1.10 and 0<y≦0.
5. The metal oxide is represented by a ratio of Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]: based on the number of atoms) in the vicinity of the surface of the first solid electrolyte layer on the air electrode side is 0.4 or more; and a ratio of Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]) in the vicinity of the surface of the first solid electrolyte layer on the hydrogen electrode side is 0.003 or more and 0.3 or less; Proton conducting cell structure.
2. 2. The proton conductive cell structure according to claim 1, wherein a ratio of Sr to a total amount of Ba and Sr (Sr / [Ba+Sr]) in a central portion in a thickness direction of the first solid electrolyte layer is 0.005 or more and 0.3 or less.
3. 3. The proton conductive cell structure according to claim 1, wherein a ratio of Sr to a total amount of Ba and Sr (Sr / [Ba+Sr]) in a region of 6% of a total thickness of the first solid electrolyte layer from a surface on an air electrode side toward a hydrogen electrode side in a thickness direction is 0.3 or more.
4. In the formula (1), Element A is 50 at % or more Zr, 4. The proton conductive cell structure according to claim 1, wherein the element M is Y.
5. the solid electrolyte layer further includes a second solid electrolyte layer interposed between the first solid electrolyte layer and the air electrode and made of a porous material; The second solid electrolyte layer is It has a perovskite structure and the following formula (1): Ba x1 Sr x2 A 1-y M y O 3-δ (1) (In the formula, element A is at least one selected from the group consisting of Zr, Ce, and Hf, The element M is at least one selected from the group consisting of Y, Yb, Er, Ho, Tm, Gd, In, and Sc; δ is the amount of oxygen deficiency, and satisfies 0.95≦x1+x2≦1.10 and 0<y≦0.
5. The proton conductive cell structure according to claim 1 , comprising a metal oxide represented by the formula:
6. In the formula (1), Element A is 50 at % or more Zr, 6. The proton conducting cell structure according to claim 5, wherein the element M is Y.
7. A proton conductor used as the first solid electrolyte layer in the proton conductive cell structure according to claim 1, It is a layered material made of a dense material, It has a perovskite structure and the following formula (1): Ba x1 Sr x2 A 1-y M y O 3-δ (1) (In the formula, element A is at least one selected from the group consisting of Zr, Ce, and Hf, The element M is at least one selected from the group consisting of Y, Yb, Er, Ho, Tm, Gd, In, and Sc; δ is the amount of oxygen deficiency, and satisfies 0.95≦x1+x2≦1.10 and 0<y≦0.
5. The metal oxide is represented by A ratio of Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]: based on the number of atoms) in the vicinity of the first main surface is 0.4 or more, and a ratio of Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]) in the vicinity of the second main surface is 0.003 or more and 0.3 or less; Proton conductor.
8. 8. The proton conductor according to claim 7, wherein a ratio of Sr to the total amount of Ba and Sr (Sr / [Ba+Sr]) in a central portion in a thickness direction is 0.005 or more and 0.3 or less.
9. 9. The proton conductor according to claim 7, wherein a ratio of Sr to a total amount of Ba and Sr (Sr / [Ba+Sr]) in a region of 6% of a total thickness from the first main surface side toward the second main surface side in a thickness direction is 0.3 or more.
10. In the formula (1), Element A is 50 at % or more Zr, The proton conductor according to claim 7 , wherein the element M is Y.
11. An electrochemical device comprising the proton-conducting cell structure according to any one of claims 1 to 6.
12. A method for producing a proton conductor used as the first solid electrolyte layer of the proton conductive cell structure according to any one of claims 1 to 4, comprising the steps of: It has a perovskite structure and the following formula (2): Ba x1 A 1-y M y O 3-δ (2) (In the formula, element A is at least one selected from the group consisting of Zr, Ce, and Hf, The element M is at least one selected from the group consisting of Y, Yb, Er, Ho, Tm, Gd, In, and Sc; δ is the amount of oxygen deficiency, and satisfies 0.95≦x1≦1.10 and 0<y≦0.
5. On the air electrode side surface of the first solid electrolyte precursor layer, It has a perovskite structure and the following formula (3): Sr x2 A 1-y M y O 3-δ (3) (In the formula, element A is at least one selected from the group consisting of Zr, Ce, and Hf, The element M is at least one selected from the group consisting of Y, Yb, Er, Ho, Tm, Gd, In, and Sc; δ is the amount of oxygen deficiency, and satisfies 0.95≦x2≦1.10 and 0<y≦0.
5. contacting a mixture of a powder of a metal oxide represented by the formula (I) with a powder of a strontium compound; In this state, heat treatment is performed at 1200 to 1400°C. A method for producing a proton conductor comprising the steps of:
13. A method for producing a proton conductor used as the solid electrolyte layer of the proton conducting cell structure according to claim 5 or 6, comprising the steps of: It has a perovskite structure and the following formula (2): Ba x1 A 1-y M y O 3-δ (2) (In the formula, element A is at least one selected from the group consisting of Zr, Ce, and Hf, The element M is at least one selected from the group consisting of Y, Yb, Er, Ho, Tm, Gd, In, and Sc; δ is the amount of oxygen deficiency, and satisfies 0.95≦x1≦1.10 and 0<y≦0.
5. On the air electrode side surface of the first solid electrolyte precursor layer, It has a perovskite structure and the following formula (3): Sr x2 A 1-y M y O 3-δ (3) (In the formula, element A is at least one selected from the group consisting of Zr, Ce, and Hf, The element M is at least one selected from the group consisting of Y, Yb, Er, Ho, Tm, Gd, In, and Sc; δ is the amount of oxygen deficiency, and satisfies 0.95≦x2≦1.10 and 0<y≦0.
5. A paste containing a powder of a metal oxide represented by the formula (I) and a powder of a strontium compound and a binder is applied to the substrate. In this state, heat treatment is performed at 1200 to 1400°C. A method for producing a proton conductor comprising the steps of:
Citation Information
Patent Citations
Ionic conductor
JP2001307546A
Mixed ion conductor and device using the same
JP2007197315A
Perovskite type composite oxide thin film
JP2009231075A
Solid oxide fuel battery
JP2016103409A
Method for producing ceramic, capacitor, solid oxide type fuel cell, water electrolytic device and hydrogen pump
JP2016160111A